2013 IEEE Seventh International Symposium on Service-Oriented System Engineering 2013
DOI: 10.1109/sose.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

The Design of Cloud-Based 4G/LTE for Mobile Augmented Reality with Smart Mobile Devices

Abstract: The system characteristics of 4G and beyond 4G broadband mobile system (BMS) are high data rate (throughput), low latency (delay), high mobility (speed), and high capacity. The current recognized 4G BMS needs to meet the requirements specified by IMT-Advanced of ITU-T.Those BMSs include 3GPP-LTE/LTE-Advanced and IEEE 802.16e/m (WiMAX 1/WiMAX 2). In the meantime, the smart device (smartphone and tablet) with powerful CPU/GPU, HD digital camera, digital compass, GPS, and various sensors are becoming rapidly popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 9 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Servers were built in the cloud by using Amazon Web Services cloud platform. A similar study has conducted by Bao-Shuh P. Lin et al [14], in which, they used cloud-based 4G broadband mobile system (BMS) (TD-LTE) to develop mobile augmented reality (MAR) applications. They addressed a design of navigation/tourism applications for indoor and outdoor, collaborative urban design, and multiuser interactive motion learning system.…”
Section: Related Workmentioning
confidence: 94%
See 1 more Smart Citation
“…Servers were built in the cloud by using Amazon Web Services cloud platform. A similar study has conducted by Bao-Shuh P. Lin et al [14], in which, they used cloud-based 4G broadband mobile system (BMS) (TD-LTE) to develop mobile augmented reality (MAR) applications. They addressed a design of navigation/tourism applications for indoor and outdoor, collaborative urban design, and multiuser interactive motion learning system.…”
Section: Related Workmentioning
confidence: 94%
“…• Pervasive mobile computing and cloud computing (light-weight applications) to overcome processing power limitation [13][14][15][16].…”
Section: Related Workmentioning
confidence: 99%
“…Based on the platform, many applications were introduced. For example, research [11] investigated the roles of 5G in the development of cloud, big data, SDN, and IoT, and then it proposed an integrated architecture of these technologies for 5G; research [12] addressed the technology outlook of computing power and system characteristics of 5G Mobile broadband system; research [13] described and implemented cloud computing for various Mobile Augmented Reality (MAR) applications with smart mobile devices; research [14] showed the challenges of applying SDN/NFV to 5G and IoT. [15][16] investigated various ML algorithms to cluster, forecast, and manage handover behaviors and traffic behaviors of a huge number of cells based on analyzing a huge amount of collected data.…”
Section: Experimental Architecture Based On Big Data ML and Sdn/nfv mentioning
confidence: 99%
“…The integration of cloud computing, mobile clients (such as the smart mobile devices including the smartphones and tablets), servers and data center [4][5][6]9,19,23] and logistics management [24] could be applied for the precast supply chain management. As illustrated in Figure 1, the architectural system of cloud computing for the precast supply chain management is illustrated.…”
Section: Cloud Computing System Architecture Within the Precast Constmentioning
confidence: 99%